I'll see you in court - Grace, Philippa ([S.l.] : Inns Court School of Law [production company] ; London : Blackstone Press, 1995)
This video, the fourth in the series, examines, discusses what is required to be an effective negotiator.
A Michael Barratt Limited Production for The Inns of Court School of Law
Series editor, Rosemary Samwell-Smith ; writers, Susannah Leahy, Margot Taylor
Keywords: Negotiation -- Legal status, laws, etc